2016
DOI: 10.1128/aac.01868-15
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Colistin Methanesulfonate and Colistin in Critically Ill Patients with Acute Renal Failure Requiring Intermittent Hemodialysis

Abstract: Colistin is increasingly used as a last option for the treatment of severe infections due to Gram-negative bacteria in critically ill patients requiring intermittent hemodialysis (HD) for acute renal failure. Our objective was to characterize the pharmacokinetics (PK) of colistin and its prodrug colistin methanesulfonate (CMS) in this population and to suggest dosing regimen recommendations. Eight intensive care unit (ICU) patients who were under intermittent HD and who were treated by CMS (Colimycine) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 21 publications
(54 reference statements)
1
39
0
2
Order By: Relevance
“…In this vein, polymyxin‐type antibiotics are increasingly used to treat CF. However, most PK studies of intravenous polymyxin B are in critically ill patients or animal models, and we are not aware of any studies that have described polymyxin B PK in patients with CF . In adult patients without CF, renal clearance is a minor elimination pathway for polymyxin B, but less is known about the pharmacokinetics of polymyxin B in patients with CF .…”
mentioning
confidence: 99%
“…In this vein, polymyxin‐type antibiotics are increasingly used to treat CF. However, most PK studies of intravenous polymyxin B are in critically ill patients or animal models, and we are not aware of any studies that have described polymyxin B PK in patients with CF . In adult patients without CF, renal clearance is a minor elimination pathway for polymyxin B, but less is known about the pharmacokinetics of polymyxin B in patients with CF .…”
mentioning
confidence: 99%
“…Colistin methanesulfonate and formed colistin are efficiently cleared by intermittent and continuous renal support modalities; less information is available for SLED than for shorter forms of IHD and CRRT . Supplementary doses of CMS are needed for patients receiving IHD or SLED.…”
Section: Clinical Questions and Recommendationsmentioning
confidence: 99%
“…Apparent clearance of colistin and hence the dose requirements of CMS are greater in patients on CRRT than for patients with normal renal function . Detailed dose suggestions for patients receiving renal support have been proposed …”
Section: Clinical Questions and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…And it's also indicated that to achieve colistin plasma concentrations at the steady state considered adequate (2.5 mg/L), the colistin methanesulfonate sodium maintenance dose during CRRT had to be similar to or even higher than that used in patients with preserved kidney function (73,77). For patients receiving intermittent RRT, it's suggested to give an additional dose of colistin methanesulfonate sodium after dialysis (77,88), but no standardized dose recommendations are currently available for these long-lasting modalities of intermittent RRT. For end-stage renal disease (ESRD) patients receiving intermittent hemodialysis (HD), evidence from 10 patients indicated that HD should be conducted at the end of a dosing interval and a supplemental dose should be administered (89).…”
Section: Dosing Strategiesmentioning
confidence: 99%